2011
DOI: 10.1038/hr.2011.175
|View full text |Cite
|
Sign up to set email alerts
|

Novel mechanism of angiotensin II-induced cardiac injury in hypertensive rats: the critical role of ASK1 and VEGF

Abstract: This study was undertaken to elucidate a novel mechanism underlying angiotensin II-induced cardiac injury, focusing on the role of oxidative stress and myocardial capillary density. Salt-loaded Dahl salt-sensitive hypertensive rats (DS rats), a useful model for hypertensive cardiac remodeling or heart failure, were orally given irbesartan (an AT1 receptor blocker), tempol (a superoxide dismutase mimetic) or hydralazine (a vasodilator). Irbesartan significantly ameliorated left ventricular ischemia and prevente… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
34
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(38 citation statements)
references
References 20 publications
3
34
0
1
Order By: Relevance
“…It has been confirmed that O 2 ‾ is the dominant ROS species in ACE2 KO heart (Oudit et al, 2007). Interestingly, Nako et al reported that irbesartan (AT1R blocker) and Tempol (free radical scavenger) display the same 52 cardioprotective effects against Ang II induced cardiac injury (Nako et al, 2012). Present study results show that there was enhanced O 2 ‾ production in the myocardium and aorta of ACE2 KO mice infused with Ang II.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…It has been confirmed that O 2 ‾ is the dominant ROS species in ACE2 KO heart (Oudit et al, 2007). Interestingly, Nako et al reported that irbesartan (AT1R blocker) and Tempol (free radical scavenger) display the same 52 cardioprotective effects against Ang II induced cardiac injury (Nako et al, 2012). Present study results show that there was enhanced O 2 ‾ production in the myocardium and aorta of ACE2 KO mice infused with Ang II.…”
Section: Discussionsupporting
confidence: 70%
“…Support is greatest for the first theory (Crackower et al, 2002;Nakamura et al, 2008;Nako et al, 2012), however, there is still evidence that Ang (1-7) is essential for maintenance of normal cardiac function by counteracting Ang II induced hypertrophic effects (Grobe et al, 2007;Kassiri et al, 2009b There are questions as to the mechanisms by which Ang II induces cardiac injury. One proposed mechanism is increased sarcolemmic and microvascular permeability leading to cardiac myocyte death (Gavras & Gavras, 2002b).…”
Section: Discussionmentioning
confidence: 99%
“…Our findings, together with those of others, [29][30][31][32][33][34][35][36][37] do not support further evaluation of combination treatment with bevacizumab plus R-CHOP in patients with DLBCL. Indeed, it has been suggested that the tumor microenvironment may be predictive of a response to bevacizumab in DLBCL, and that bevacizumab may only be beneficial in DLBCL with high relative expression of a suite of endothelial markers and angiogenic regulators (the 'stromal-2' signature) that is associated with increased tumor blood vessel density.…”
Section: Discussionmentioning
confidence: 29%
“…33 VEGF, in turn, has a cardioprotective role. It is up-regulated in both animal and human hearts exposed to hypoxic conditions [34][35][36] and can prevent oxidative stress-induced apoptosis of endothelial cells in vitro. 29 Thus, it may be that bevacizumab is not directly toxic to the heart, but rather its inhibition of endothelial VEGF expression prevents the ability of VEGF to counter the negative effects of doxorubicin.…”
Section: Discussionmentioning
confidence: 99%
“…Reactive oxygen species-induced activation of apoptosis signalregulating kinase 1 (ASK1) plays crucial roles in oxidative stressmediated cell death [51]. Nako et al reported that VEGF treatment prevents oxidative stress-induced endothelial apoptosis by inhibiting activation of ASK [52]. In addition, VEGF upregulates the expression of Becn1, which is an autophagy-related gene [44].…”
Section: Resultsmentioning
confidence: 99%